2022
DOI: 10.3390/mi13010115
|View full text |Cite
|
Sign up to set email alerts
|

A Low Cost Fe3O4–Activated Biochar Electrode Sensor by Resource Utilization of Excess Sludge for Detecting Tetrabromobisphenol A

Abstract: Owing to its ubiquity in natural water systems and the high toxicity of its accumulation in the human body, it is essential to develop simple and low-cost electrochemical sensors for the determination of 3,3′,5,5′-tetrabromobisphenol A (TBBPA). In this work, Fe3O4–activated biochar, which is based on excess sludge, was prepared and characterized using scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), Fourier transform infrared spectroscopy (FTIR) and BET analysis to analyze its basic fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Aer the addition of 0.5 mM glucose, the oxidation potential appeared at 0.50 V, related to the electrocatalytic oxidation of glucose occurring on NiS-NiS 2 /sludge-based biochar/GCE, corresponding to the reaction equation as follow: The high response current of NiS-NiS 2 /sludge-based biochar/GCE for detecting glucose was mainly caused by the synergistic effects of NiS-NiS 2 and sludge-based biochar. On the one hand, unique porous structure as well as abundant functional groups of sludge-based biochar 30 provided strong adsorption capacity and abundant electrocatalytic active site for glucose detection. On the other hand, the high conductivity of NiS may further enhance its electrocatalytic performance in glucose analysis process.…”
Section: Electrochemical Behaviors Of the Three Kinds Of Modied Elec...mentioning
confidence: 99%
“…Aer the addition of 0.5 mM glucose, the oxidation potential appeared at 0.50 V, related to the electrocatalytic oxidation of glucose occurring on NiS-NiS 2 /sludge-based biochar/GCE, corresponding to the reaction equation as follow: The high response current of NiS-NiS 2 /sludge-based biochar/GCE for detecting glucose was mainly caused by the synergistic effects of NiS-NiS 2 and sludge-based biochar. On the one hand, unique porous structure as well as abundant functional groups of sludge-based biochar 30 provided strong adsorption capacity and abundant electrocatalytic active site for glucose detection. On the other hand, the high conductivity of NiS may further enhance its electrocatalytic performance in glucose analysis process.…”
Section: Electrochemical Behaviors Of the Three Kinds Of Modied Elec...mentioning
confidence: 99%
“…Biochar’s porous structure gives it a larger specific surface area for absorbing target analyte and carrying or loading various activate molecules or materials, such as copper hexacyanoferrate [ 9 ], Fe 3 O 4 [ 35 ], MoSe 2 [ 36 ], and nickel hydroxide [ 37 ]. These materials’ good properties in various aspects of spatial structure, redox ability, magnetism, or conductivity enhance and improve the analytical performance of biochar-based sensors.…”
Section: The Role Of Biochar In the Fabrication Of Electrochemical Se...mentioning
confidence: 99%
“…Luo et al, developed a simple and cost-effective electrochemical sensor based on an Fe 3 O 4 -activated biochar. The proposed sensor showed excellent electrochemical performance toward TBBPA-sensing when compared to separate precursor materials [ 35 ]. The electrochemical test results revealed that the Fe 3 O 4 -activated biochar film exhibited a lower charged transfer resistance, a larger active surface area, and a higher accumulation efficiency toward TBBPA.…”
Section: The Application Of Electrochemical Sensors and Biosensors Ba...mentioning
confidence: 99%
“…Graphene oxide and Fe 3 O 4 have been utilized for the adsorption of heavy metals, environmental pollutants, , and biomolecules. , The presence of magnetic nanoparticles on graphene sheets effectively prevents self-agglomeration, leading to improved surface area for target analyte binding. , Graphene magnetic nanocomposites have been applied in electrochemistry , and mass spectrometry to improve the selectivity and sensitivity of detection systems . Furthermore, it has been reported that Fe 3 O 4 /GO can selectively bind with pesticides, leading to selective pesticide detection . The −OH groups of GO can act as a H-donor and acceptor, resulting in strong H-bonding with CBF and CBZ .…”
Section: Introductionmentioning
confidence: 99%